Implementasi Blockchain berbasis BigchainDB dan Tendermint pada Sistem Penyimpanan Data IoT - Immanuel Sibarani; Eko Sakti Pramukantoro; Fariz Andri Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The IoT data storage system in general is centralized so that the data generated by the IoT sensor are stored on one data storage only. Centralized systems are susceptible to failure, which can cause the entire system to crash and can cause data loss because there are no backups. Therefore, in this study, we will propose a decentralized storage system using blockchain. The Blockchain is a decentralized, distributed, and immutable database that stores assets and lists of transactions in peer-to-peer (blockchain) networks. The Blockchain can replicate data to be stored on many nodes in the blockchain network. If there is a system failure on one node, the node will not affect the system on the other node. This research focuses on implementing blockchain on IoT data storage systems using BigchainDB and Tendermint. BigchainDB and Tendermint are the right applications to implement blockchain on MongoDB-based IoT data storage systems. The results of functional testing show that the decentralized IoT data storage system is running by its function in storing data and replicating data on several data storage areas. Based on these results, the system in this study can be a solution for centralized IoT data storage systems.